Extreme low flow and water quality – a long-term view on the River Elbe - Hübner, Gerd; Schwandt, Daniel (ERDKUNDE, 2018)
Effects of extreme low flow on the water quality of the River Elbe (Germany) were assessed by the example of the summer low flow events in 1904, 1911, 1921, 1934, 1935, 1952, 1964, 2003, and 2015 using numerous unpublished historical data. The month with the most pronounced low flow was usually August, except in 1934, when it was July. Oxygen content, permanganate index, chloride concentration, and water hardness of the Elbe during the low flow months were compared with the annual range. The annual maximum of these water quality parameters (or in the case of oxygen, the annual minimum) was often observed in the low flow month. Water quality during low flow corresponded to the general pollution level, most elevated in 1952 and 1964. During low flows in 2003 and 2015, the reduced input of easily oxidisable organic matter resulted in a stable oxygen regime. Chloride concentration and hardness of the Elbe were mostly determined by the tributary Saale and in 2003 and 2015 still considerably elevated against the natural background. The transferable method of a systematic comparison of several low flow events of a river over a long period of time facilitates the differentiation between event-specific influences (e.g. proportion of tributaries on the total discharge) and common influences (e.g. accumulation of substances due to a lack of dilution). At the same time, basics for characterisation and classification of former and present low flow events are provided.